Atrioventricular block as a predictor of major adverse cardiac events in acute coronary syndrome patients. (24th May 2021) - Santos, H; Santos, M; Almeida, I; Miranda, H; Sa, C; Almeida, S; Chin, J; Sousa, C; Almeida, L
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Portuguese Registry of Acute Coronary Syndromes Background: Atrioventricular block (AVB) can be a consequence of ischemia in acute coronary syndrome (ACS). Then, its expected, that AVB occurrence is associated with higher rates of major adverse cardiac events (MACE). Objective: Evaluate if sustained AVB was a predictor of MACE in ACS hospitalized patients. Methods: Multicenter retrospective study, based on the Portuguese Registry of ACS between 1/10/2010-3/05/2020. Patients were divided into two groups: A – patients without AVB, and B – patients that presented AVB. Were excluded patients without a previous cardiovascular history or clinical data regarding AVB occurrence. MACE was defined as re-infarction, congestive heart failure, cardiogenic shock, a mechanical complication of myocardial infarction, completed atrioventricular block, sustained ventricular tachycardia, cardiac arrest, stroke, major hemorrhage, transfusion and hospitalization death. Univariate logistic regression was performed to assess if AVB in ACS patients was a predictor of MACE. Results: A total of 32157 patients was analyze and 23774 had information regarding AVB. From the group of patients that presented AVB, 214 (0.9%) had re-infarction, 3847 (16.2%) had congestive heart failure, 1018 (4.3%) had cardiogenic shock, 1069 (4.5%) had atrial fibrillation, 152 (0.6%) had a mechanical complication of myocardial infarction, 354 (1.5%) had sustained ventricular tachycardia, 706 (3.0%) had cardiac arrest, 152 (0.6%) had stroke, 364 (1.5%) had major hemorrhage, 353 (1.5%) had blood transfusion and 928 (3.0%) died. AVB did not predict re-infarction (p = 0.145), congestive heart failure (p = 0.334), atrial fibrillation (p = 0.171), mechanical complication of myocardial infarction (p = 0.465) and cardiac arrest (p = 0.142). Logistic regression revealed that AVB in ACS patients was a predictor of cardiogenic shock (odds ratio (OR) 2.350, p = 0.012, confidence interval (CI) 1.207-4.572), sustained ventricular tachycardia (OR 2.269, p = 0.013, CI 1.187-4.340), stroke (OR 2.231, p < 0.001, CI 1.779-5.852), major hemorrhage (OR 3.863, p < 0.001, CI 2.667-5.558), blood transfusion (OR 4.291, p < 0.001, CI 3.002-6.137) and hospitalization death (OR 2.699, p < 0.001, CI 1.725-4.222). Conclusions: AVB in ACS patients predict MACE, namely cardiogenic shock, sustained ventricular tachycardia, stroke, major hemorrhage, blood transfusion and hospitalization death.